LPSO and dual-scale particle synergistically enhanced Mg-Gd series heat-resistant alloy and preparation method thereof
By introducing Al2Gd microparticles and TiB2 nanoparticles into Mg-Gd alloys, combining zinc elements and using hot extrusion technology, the problem of poor mechanical properties of magnesium alloys is solved, significantly improving its room temperature and high temperature strength, and broadening the application range , realizes the availability of magnesium alloys in the aerospace and defense fields.
Patent Information
- Application Number
- CN202411455820.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-14
AI Technical Summary
The mechanical properties of magnesium alloys are poor, especially at high temperatures, which limit their application in aerospace and defense fields. The existing ceramic particle-reinforced magnesium-based composite materials have problems of poor agglomeration and interface bonding strength. The Mg-Gd alloys are The mechanical properties of room temperature and high temperature still need to be further improved.
The Mg-Gd-type alloy is synergistically enhanced by LPSO and double-scale particles. By introducing Al2Gd microparticles and TiB2 nanoparticles into the Mg-Gd alloy, combining zinc elements, and preparing them by hot extrusion technology, forming a good dispersed structure and improving the alloy. room temperature and high temperature intensity.
The room temperature and high temperature yield strength and tensile strength of Mg-Gd series alloys have been significantly improved, and the application range has been broadened, making them suitable for key components in the aerospace and defense fields, and the preparation process is simple and the cost is low.
Smart Images

Figure CN119307796A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnesium alloys, and in particular to a Mg-Gd series heat-resistant alloy synergistically reinforced by LPSO and dual-scale particles and a preparation method thereof. Background Art
[0002] Magnesium alloys have the characteristics of low density, high specific strength and high specific stiffness, and have received extensive attention in the fields of automobiles, national defense science and technology, aerospace, and electronics. However, due to the poor mechanical properties of magnesium alloys, their further promotion and application are limited. For example, the widely used magnesium alloy AZ91 (Mg-9wt%Al-0.6wt%Zn) has high room temperature strength, but poor high temperature creep performance, and the use temperature cannot exceed 120°C; another common magnesium alloy AE42 (Mg-4wt%Al-2wt%RE) has good high temperature mechanical strength and can reach an operating temperature of 175°C, but its room temperature strength is low. In order to expand the application range of magnesium alloys, people are constantly designing magnesium alloys with excellent mechanical properties. Some researchers have tried to improve the mechanical properties of magnesium alloys by introducing ceramic particles. However, ceramic particle reinforced magnesium-based composites are prone to ceramic particle agglomeration and poor ceramic particle-magnesium matrix interface bonding strength.
[0003] In recent years, Mg-RE alloys have become a research hotspot due to their good properties, among which Mg-Gd alloys have attracted much attention due to their good solid solution strengthening and aging strengthening effects. However, relevant studies have shown that the addition of gadolinium to Mg-Gd binary alloys is usually higher than 10% to produce significant aging strengthening effects, and the addition of a large amount of gadolinium will increase the cost of the alloy, and the mechanical properties of the current Mg-Gd alloys at room temperature and high temperature still need to be further improved. Summary of the invention
[0004] In view of this, the present invention provides a Mg-Gd heat-resistant alloy synergistically enhanced by LPSO and dual-scale particles and a preparation method thereof. The Mg-Gd heat-resistant alloy provided by the present invention has good room temperature and high temperature strength, and the preparation method is simple and low in cost.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] A Mg-Gd heat-resistant alloy synergistically reinforced by LPSO and dual-scale particles, comprising the following components in mass percentage: Gd 8.0-10.0wt.%, TiB2 0.3-0.9wt.%, Al2Gd 2.74-8.21wt.%, Zn 0.4-1.0wt.%, and the balance is Mg; wherein Al2Gd exists in the form of Al2Gd micron particles, and the TiB2 exists in the form of TiB2 nanoparticles.
[0007] Preferably, the particle size of the TiB2 nanoparticles is 70 to 110 nm, and the particle size of the Al2Gd micron particles is 1.1 to 12.3 μm.
[0008] The present invention provides a method for preparing the Mg-Gd heat-resistant alloy synergistically reinforced by LPSO and dual-scale particles as described in the above scheme, comprising the following steps:
[0009] The magnesium, magnesium-gadolinium master alloy, zinc and TiB2 / Al master alloy are heated and melted, and the obtained alloy liquid is cast to obtain an ingot;
[0010] The ingot is homogenized to obtain an ingot;
[0011] The billet is hot extruded to obtain the Mg-Gd series heat-resistant alloy synergistically reinforced by the LPSO and the dual-scale particles.
[0012] Preferably, the purity of the magnesium is above 99.8%; the magnesium-gadolinium master alloy is Mg-30wt.%Gd, and the purity of the magnesium-gadolinium master alloy is above 99.9%; the mass ratio of TiB2 to Al in the TiB2 / Al master alloy is 30:70; the zinc is zinc particles, and the purity of the zinc particles is above 99.8%;
[0013] The mass ratio of gadolinium, zinc and TiB2 / Al master alloy in the pure magnesium and magnesium-gadolinium master alloy is (86.6-90.6):9:(0.4-1):(0-3), and the mass of the TiB2 / Al master alloy is not 0.
[0014] Preferably, the preparation method of the TiB2 / Al intermediate alloy comprises: ball milling TiB2 and aluminum powder and then hot pressing and sintering to obtain the TiB2 / Al intermediate alloy; the rotation speed of the ball mill is 100r / min, and the ball-to-material ratio is 3:1; the temperature of the hot pressing and sintering is 630-650°C, and the time is 30-60min.
[0015] Preferably, the heating and melting of magnesium, magnesium-gadolinium master alloy zinc and TiB2 / Al master alloy comprises: firstly heating and melting magnesium under the protection of mixed gas, and then sequentially adding magnesium-gadolinium master alloy, zinc and TiB2 / Al master alloy for second heating and melting;
[0016] The mixed gas includes CO2 and SF6, the volume fraction of CO2 in the mixed gas is 99%, and the volume fraction of SF6 is 1%; the temperature of the first heating and melting is 680-700°C; the temperature of the second heating and melting is 760-800°C.
[0017] Preferably, the casting temperature is 720-730°C.
[0018] Preferably, the homogenization treatment is carried out at a temperature of 510° C. and for a time of 12 h.
[0019] Preferably, the hot extrusion temperature is 410° C. and the extrusion ratio is 18:1.
[0020] Preferably, the magnesium, magnesium-gadolinium master alloy and TiB2 / Al master alloy are polished before use.
[0021] The present invention provides a Mg-Gd series heat-resistant alloy synergistically enhanced by LPSO and dual-scale particles, comprising the following components in mass percentage: Gd 8.0-10.0wt.%, TiB2 0.3-0.9wt.%, Al2Gd 2.74-8.21wt.%, Zn 0.4-1.0wt.%, and the balance is Mg; wherein Al2Gd exists in the form of Al2Gd micron particles, and the TiB2 exists in the form of TiB2 nanoparticles. The present invention introduces LPSO phase and dual-scale particles (i.e., Al2Gd micron particles and TiB2 nanoparticles) into the Mg-Gd series alloy, and significantly improves the room temperature strength and high temperature strength of the Mg-Gd series alloy through the synergistic effect of the LPSO phase, Al2Gd micron particles and TiB2 nanoparticles, especially improves the high temperature yield strength and high temperature tensile strength at 200-300°C, broadens the application range of the magnesium alloy, and enables it to be used in key parts in the fields of aerospace and national defense. The results of the embodiments show that the Mg-Gd heat-resistant alloy ((0.6wt.%TiB2-5.47wt.%Al2Gd) / Mg-9Gd-1.0Zn) prepared by the present invention has a yield strength of 317MPa and a tensile strength of 243MPa at room temperature, a yield strength of 390MPa and a tensile strength of 303MPa at 200℃, a yield strength of 224MPa and a tensile strength of 196MPa at 300℃.
[0022] The present invention also provides a method for preparing the Mg-Gd series heat-resistant alloy synergistically enhanced by LPSO and dual-scale particles described in the above scheme. The present invention introduces LPSO phase and TiB2 nanoparticles into the Mg-Gd series alloy by adding zinc and TiB2 / Al master alloy, and at the same time, the Al element reacts with the Gd element to generate in-situ Al2Gd micron particles with good thermal stability. The introduced TiB2 nanoparticles have a clean interface with the Mg matrix without inclusions, and have a high degree of lattice matching with the Mg matrix, which plays a role in refining the α-Mg grains. At the same time, they can be used as a high-melting point hard second phase to pin dislocation movement and grain boundary sliding, thereby improving the thermal stability of the organization; Al2Gd micron particles act as heterogeneous nucleation sites to refine the alloy organization while improving the distribution of the Mg-Y phase, thereby significantly improving the high-temperature mechanical properties of the magnesium alloy. Moreover, in the present invention, during the smelting process, there is no need to use additional mechanical stirring, ultrasonic dispersion and other means to obtain TiB2 nanoparticles with good dispersion, Al2Gd micron particles and Mg-Gd heat-resistant alloys synergistically enhanced by the LPSO phase. The preparation process is simple, easy to promote, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The scanning electron microscope images of the Mg-9Gd matrix alloy, Mg-9Gd-1Zn, (0.6wt.%TiB2-5.47wt.%Al2Gd) / Mg-9Gd and (0.6wt.%TiB2-5.47wt.%Al2Gd) / Mg-9Gd-1.0Zn alloys prepared in Comparative Example 1, Examples 4, 6 and 8, wherein (a) is the scanning electron microscope image of the Mg-9Gd matrix alloy prepared in Comparative Example 1. Scanning electron microscope images, (b) is a scanning electron microscope image of the extruded Mg-9Gd-1Zn alloy of Example 4, (c) is a scanning electron microscope image of the extruded (0.6wt.%TiB2-5.47wt.%Al2Gd) / Mg-9Gd alloy of Example 6, (d) is a scanning electron microscope image of the extruded (0.6wt.%TiB2-5.47wt.%Al2Gd) / Mg-9Gd-1Zn alloy of Example 8;
[0024] Figure 2 Tensile engineering stress-strain curves of Mg-9Gd, Mg-9Gd-1.0Zn, (0.6wt.%TiB2-5.47wt.%Al2Gd) / Mg-9Gd, (0.6wt.%TiB2-5.47wt.%Al2Gd) / Mg-9Gd-1.0Zn alloys prepared in Comparative Example 1, Examples 4, 6, and 8 at room temperature;
[0025] Figure 3Tensile engineering stress-strain curves at 200° C. for the Mg-9Gd matrix alloy prepared in Comparative Example 1 and the (0.6wt.% TiB2-3.71wt.% Al2Gd) / Mg-9Gd-1.0Zn alloy prepared in Example 8;
[0026] Figure 4 Tensile engineering stress-strain curves at 250°C for the Mg-9Gd matrix alloy prepared in Comparative Example 1 and the (0.6wt.% TiB2-3.71wt.% Al2Gd) / Mg-9Gd-1.0Zn alloy prepared in Example 8;
[0027] Figure 5 Tensile engineering stress-strain curves at 300°C of the Mg-9Gd matrix alloy prepared in Comparative Example 1 and the (0.6wt.% TiB2-3.71wt.% Al2Gd) / Mg-9Gd-1.0Zn alloy prepared in Example 8. DETAILED DESCRIPTION
[0028] The present invention provides a Mg-Gd series heat-resistant alloy synergistically reinforced by LPSO and dual-scale particles, comprising the following components in mass percentage: Gd 8.0-10.0wt.%, TiB2 0.3-0.9wt.%, Al2Gd 2.74-8.21wt.%, Zn 0.4-1.0wt.%, and the balance is Mg; wherein Al2Gd exists in the form of Al2Gd micron particles, and the TiB2 exists in the form of TiB2 nanoparticles.
[0029] In the present invention, the LPSO and dual-scale particle synergistically reinforced Mg-Gd series heat-resistant alloy preferably includes the following components in mass percentage: Gd 9wt.%, TiB2 0.5-0.8wt.%, Al2Gd 5-6wt.%, Zn 0.6-1.0wt.%, and the balance is Mg.
[0030] As a specific embodiment of the present invention, the LPSO and dual-scale particle synergistically reinforced Mg-Gd series heat-resistant alloy includes the following components in mass percentage: Gd 9wt.%, TiB2 0.6wt.%, Al2Gd 5.47wt.%, Zn 1.0wt.%, and the balance is Mg.
[0031] In the present invention, the particle size of the TiB2 nanoparticles is 70-110 nm, and the average size is preferably 98 nm. The particle size of the Al2Gd micron particles is 1.1-12.3 μm.
[0032] The present invention also provides a method for preparing the Mg-Gd heat-resistant alloy synergistically reinforced by LPSO and dual-scale particles as described in the above scheme, comprising the following steps:
[0033] The magnesium, magnesium-gadolinium master alloy, zinc and TiB2 / Al master alloy are heated and melted, and the obtained alloy liquid is cast to obtain an ingot;
[0034] The ingot is homogenized to obtain an ingot;
[0035] The billet is hot extruded to obtain the Mg-Gd series heat-resistant alloy synergistically reinforced by the LPSO and the dual-scale particles.
[0036] The present invention heats and melts magnesium, magnesium-gadolinium master alloy, zinc and TiB2 / Al master alloy, and casts the obtained alloy liquid to obtain an ingot. In the present invention, the purity of the magnesium is preferably 99.8% or more; the magnesium-gadolinium master alloy is preferably Mg-30wt.%Gd, and the purity of the magnesium-gadolinium master alloy is preferably 99.9% or more; in the present invention, the mass ratio of TiB2 to Al in the TiB2 / Al master alloy is preferably 30:70; the particle size of TiB2 in the TiB2 / Al master alloy is 70-110nm, and the average size is preferably 98nm; the zinc is preferably zinc particles, and the purity of the zinc particles is preferably 99.8% or more; the magnesium, magnesium-gadolinium master alloy and TiB2 / Al master alloy are preferably polished before use to remove surface stains and oxide scale by polishing.
[0037] In the present invention, the mass ratio of gadolinium, zinc and TiB2 / Al master alloy in the magnesium and magnesium-gadolinium master alloy is preferably (86.6-90.6):9:(0.4-1):(0-3), and the mass of the TiB2 / Al master alloy is not 0. Specifically, the mass ratio of gadolinium, zinc and TiB2 / Al master alloy in the magnesium and magnesium-gadolinium master alloy can be (87-89):9:(0.6-1):(1-2.5), more specifically 88:9:1:2; the masses of the magnesium, magnesium-gadolinium master alloy and the TiB2 / Al master alloy are all measured by the mass after grinding.
[0038] In the present invention, the preparation method of the TiB2 / Al intermediate alloy preferably includes: ball milling TiB2 and aluminum powder and then hot pressing and sintering to obtain the TiB2 / Al intermediate alloy; the rotation speed of the ball mill is preferably 100r / min, and the ball-to-material ratio is preferably 3:1; the temperature of the hot pressing and sintering is preferably 630-650°C, and the time is preferably 30-60min; the size of the TiB2 is preferably 70-110nm, and the average size is preferably 98nm; the purity of the aluminum powder is preferably above 99.5%, the size of the aluminum powder is preferably 9-13μm, and the average size is preferably 10μm.
[0039] In the present invention, the heating and melting of pure magnesium, magnesium-gadolinium master alloy, zinc and TiB2 / Al master alloy comprises: firstly heating and melting pure magnesium under the protection of mixed gas, and then sequentially adding magnesium-gadolinium master alloy, zinc and TiB2 / Al master alloy for second heating and melting; the mixed gas preferably comprises CO2 and SF6, the volume fraction of CO2 in the mixed gas is preferably 99%, and the volume fraction of SF6 is preferably 1%; the temperature of the first heating and melting is preferably 680-700°C, specifically 680°C, 690°C or 700°C; the temperature of the second heating and melting is preferably 760-800°C, specifically 760°C, 770°C, 780°C, 790°C or 800°C; after the second melting, preferably keeping warm for 15-20 minutes, then stirring and removing slag, and then casting.
[0040] In the present invention, the casting temperature is preferably 720-730° C.; in a specific embodiment of the present invention, the diameter of the ingot is 85 mm.
[0041] After obtaining the ingot, the present invention performs a homogenization treatment on the ingot to obtain a billet. In the present invention, the temperature of the homogenization treatment is preferably 510° C. and the time is preferably 12 hours. After the homogenization treatment, the ingot is preferably air-cooled to room temperature to obtain a billet.
[0042] After obtaining the billet, the present invention performs hot extrusion on the billet to obtain the Mg-Gd heat-resistant alloy synergistically reinforced by the LPSO and dual-scale particles. In the present invention, the temperature of the hot extrusion is preferably 410°C, and the extrusion ratio is preferably 18:1; a rod is obtained after the hot extrusion; in a specific embodiment of the present invention, the diameter of the rod is 20 mm.
[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1
[0045] In this embodiment, a LPSO-strengthened Mg-Gd alloy is prepared, and the mass percentage of each component is: gadolinium (Gd) 9wt.%, zinc (Zn) 0.4wt.%, and the balance is magnesium;
[0046] The preparation method of the LPSO-strengthened Mg-Gd alloy comprises the following steps:
[0047] S1. Raw material grinding: Pure magnesium and magnesium-gadolinium master alloy are both ground to remove surface stains and oxide scales to obtain ground pure magnesium and ground magnesium-gadolinium master alloy.
[0048] Among them, the purity of pure magnesium is 99.8%; the magnesium-gadolinium intermediate alloy is Mg-30wt.%Gd, the purity of magnesium-gadolinium intermediate alloy is 99.9%, purchased from Chongqing Yuhua New Material Technology Co., Ltd.; the purity of zinc particles is 99.8%, purchased from Chongqing Yuhua New Material Technology Co., Ltd.
[0049] S2. Alloy smelting: The polished pure magnesium obtained in S1 is melted in a resistance furnace at a temperature of 700°C under the protection of a mixed gas, and then the polished magnesium-gadolinium master alloy and zinc particles obtained in S1 are added in sequence and melted again at a temperature of 780°C, and kept warm for 20 minutes, stirred to remove slag, and finally cast at a temperature of 720°C to obtain an ingot with a diameter of 85 mm.
[0050] The mixed gas consists of 99% by volume of CO2 and 1% by volume of SF6; the mass ratio of pure magnesium after grinding, gadolinium in the magnesium-gadolinium intermediate alloy after grinding, and zinc in the zinc particles is 90.6:9:0.4.
[0051] S3. Homogenization treatment: The ingot obtained in S2 is subjected to homogenization treatment at a temperature of 510° C. for 12 h. The treated ingot is air-cooled to room temperature (25° C.) to obtain an ingot.
[0052] S4. Extrusion treatment: The billet obtained in S3 is hot extruded at a temperature of 410° C. with an extrusion ratio of 18:1 to obtain an extruded rod with a diameter of 20 mm, wherein the extruded rod is a Mg-9Gd-0.4Zn alloy.
[0053] Example 2
[0054] The present embodiment prepares a LPSO-strengthened Mg-Gd alloy, which contains the following components in mass percentage: 9 wt. % of gadolinium (Gd), 0.6 wt. % of zinc (Zn), and the balance of magnesium.
[0055] The preparation method of the LPSO-strengthened Mg-Gd alloy in this embodiment is the same as that in Embodiment 1. The mass ratio of the polished pure magnesium in S2, the gadolinium in the polished magnesium-gadolinium master alloy, and the zinc in the zinc particles is 90.4:9:0.6, and the alloy material finally obtained is Mg-9Gd-0.6Zn alloy.
[0056] Example 3
[0057] The present embodiment prepares a LPSO-strengthened Mg-Gd alloy, which contains the following components in percentage by mass: 9 wt.% of gadolinium (Gd), 0.8 wt.% of zinc (Zn), and the remainder of magnesium.
[0058] The preparation method of the LPSO-strengthened Mg-Gd alloy in this embodiment is the same as that in Example 1. The mass ratio of the polished pure magnesium in S2, the gadolinium in the polished magnesium-gadolinium master alloy, and the zinc in the zinc particles is 90.2:9:0.8, and the alloy material finally obtained is Mg-9Gd-0.8Zn alloy.
[0059] Example 4
[0060] The present embodiment prepares a LPSO-strengthened Mg-Gd alloy, which contains the following components in percentage by mass: 9 wt.% of gadolinium (Gd), 1.0 wt.% of zinc (Zn), and the balance of magnesium.
[0061] The preparation method of the LPSO-strengthened Mg-Gd alloy in this embodiment is the same as that in Example 1. The mass ratio of the polished pure magnesium in S2, the gadolinium in the polished magnesium-gadolinium master alloy, and the zinc in the zinc particles is 90:9:1.0, and the alloy material finally obtained is Mg-9Gd-1.0Zn alloy.
[0062] Example 5
[0063] The present embodiment prepares a micro-nano dual-scale particle reinforced Mg-Gd alloy, which contains the following components in mass percentage: gadolinium (Gd) 9wt.%, TiB2 0.3wt.%, Al2Gd 2.74wt.%, and the balance is magnesium.
[0064] The preparation method of the above-mentioned micro-nano dual-scale particle reinforced Mg-Gd alloy comprises the following steps:
[0065] S1. Raw material grinding: Pure magnesium, magnesium-gadolinium master alloy and TiB2 / Al master alloy are all ground to remove surface stains and oxide scale to obtain ground pure magnesium, ground magnesium-gadolinium master alloy and ground TiB2 / Al master alloy.
[0066] The purity of pure magnesium is 99.8%; the magnesium-gadolinium master alloy is Mg-30wt.%Gd, the purity of the magnesium-gadolinium master alloy is 99.9%, and it is purchased from Chongqing Yuhua New Materials Technology Co., Ltd.; the preparation method of the TiB2 / Al master alloy is: TiB2 and pure aluminum powder with a mass ratio of 30:70 are ball-milled, and then hot-pressed and sintered to prepare a 30wt.% TiB2 / Al master alloy; the ball milling speed is 100r / min; the ball-to-material ratio is 3:1; the hot-pressing sintering temperature is 630-650°C, and the sintering time is 30-60min; wherein TiB2 is purchased from Shanghai Xiangtian Nanomaterial Co., Ltd., with a size of 70-110nm (average size of 98nm); pure aluminum powder is purchased from Beijing Xingrongyuan Technology Co., Ltd., with a size of 9-13μm (average size of 10μm) and a purity of 99.5%.
[0067] S2. Alloy smelting: The polished pure magnesium obtained in S1 is melted in a resistance furnace at a temperature of 700° C. under the protection of a mixed gas, and then the polished magnesium-gadolinium master alloy and the polished TiB2 / Al master alloy obtained in S1 are added and melted again at a temperature of 780° C., and kept warm for 20 minutes, stirred to remove slag, and finally cast at a temperature of 720° C. to obtain an ingot with a diameter of 85 mm.
[0068] The mixed gas is composed of 99% CO2 and 1% SF6; the mass ratio of the polished pure magnesium, the gadolinium in the polished magnesium-gadolinium master alloy and the polished TiB2 / Al master alloy is 90:9:1.
[0069] S3. Homogenization treatment: The ingot obtained in S2 is subjected to homogenization treatment at a temperature of 510° C. for 12 h. The treated ingot is air-cooled to room temperature (25° C.) to obtain an ingot.
[0070] S4, extrusion treatment: the ingot obtained in S3 is hot extruded at a temperature of 410°C and an extrusion ratio of 18:1 to obtain an extruded rod with a diameter of 20 mm. The extruded rod is a micro-nano dual-scale particle reinforced Mg-Gd alloy, namely (0.3wt.% TiB2-2.74wt.% Al2Gd) / Mg-9Gd.
[0071] Example 6
[0072] The present embodiment prepares a micro-nano dual-scale particle reinforced Mg-Gd alloy, which contains the following components in mass percentage: gadolinium 9wt.%, TiB2 0.6wt.%, Al2Gd 5.47wt.%, and the balance is magnesium.
[0073] The preparation method of the multi-scale particle reinforced Mg-Gd alloy in this embodiment is the same as that in Example 5. The mass ratio of pure magnesium after grinding in S2, gadolinium in the magnesium-gadolinium intermediate alloy, and TiB2 / Al intermediate alloy is 89:9:2, and the final alloy material is (0.6wt.%TiB2-5.47wt.%Al2Gd) / Mg-9Gd.
[0074] Example 7
[0075] The present embodiment prepares a micro-nano dual-scale particle reinforced Mg-Gd alloy, which contains the following components in mass percentage: gadolinium 9wt.%, TiB20.9wt.%, Al2Gd 8.21wt.%, and the balance is magnesium.
[0076] The preparation method of the micro-nano dual-scale particle reinforced Mg-Gd alloy in this embodiment is the same as that in Example 5. In this embodiment S2, the mass ratio of gadolinium and TiB2 / Al master alloy in the polished pure magnesium and magnesium-gadolinium master alloy is 88:9:3, and the final alloy material is (0.9wt.%TiB2-8.21wt.%Al2Gd) / Mg-9Gd.
[0077] By testing the room temperature tensile properties of the alloys prepared in Examples 1 to 4, it can be found that when the Zn content is 1.0wt.%, the room temperature mechanical properties of the alloy are the best; the room temperature tensile properties of the alloys prepared in Examples 5 to 7 are tested, and it is found that the room temperature and high temperature mechanical properties of the (0.6wt.% TiB2-5.47wt.% Al2Gd) / Mg-9Gd alloy are the best. Therefore, 1.0wt.% Zn, 0.6wt.% TiB2 and 5.47wt.% Al2Gd are added to the Mg-9Gd alloy to prepare the Mg-Gd alloy with LPSO and dual-scale particles synergistically enhanced, as shown in Example 8.
[0078] Example 8
[0079] The present embodiment prepares a Mg-Gd alloy synergistically reinforced by LPSO and dual-scale particles, wherein the Mg-Gd alloy contains the following components in percentage by mass: Gd 9wt.%, TiB2 0.6wt.%, Al2Gd 5.47wt.%, Zn 1.0wt.%, and the balance is magnesium.
[0080] The method for preparing the above-mentioned LPSO and dual-scale particle synergistically reinforced Mg-Gd alloy comprises the following steps:
[0081] S1. Raw material grinding: Pure magnesium, magnesium-gadolinium master alloy and TiB2 / Al master alloy are all ground to remove surface stains and oxide scale to obtain ground pure magnesium, ground magnesium-gadolinium master alloy and ground TiB2 / Al master alloy.
[0082] Among them, the purity of pure magnesium is 99.8%; the magnesium-gadolinium intermediate alloy is Mg-30wt.%Gd, with a purity of 99.9%, purchased from Chongqing Yuhua New Materials Technology Co., Ltd.; the purity of zinc particles is 99.8% Zn, purchased from Chongqing Yuhua New Materials Technology Co., Ltd.; the preparation method of TiB2 / Al intermediate alloy is: TiB2 with a mass ratio of 30:70 and pure aluminum powder are ball milled, and then hot pressed and sintered to prepare 30wt.% TiB2 / Al intermediate alloy; the ball milling speed is 100r / min; the ball-to-material ratio is 3:1; the hot pressing sintering temperature is 630-650°C, and the sintering time is 30-60min; Among them, TiB2 is purchased from Shanghai Xiangtian Nanomaterials Co., Ltd., with a size of 70-110nm (average size is 98nm); pure aluminum powder is purchased from Beijing Xingrongyuan Technology Co., Ltd., with a size of 9-13μm (average size is 10μm) and a purity of 99.5%.
[0083] S2. Alloy smelting: The polished pure magnesium obtained in S1 is melted in a resistance furnace at a temperature of 700° C. under the protection of a mixed gas, and then the polished magnesium-gadolinium master alloy, zinc particles and polished TiB2 / Al master alloy obtained in S1 are added in sequence and melted again at a temperature of 780° C., and kept warm for 20 minutes, stirred to remove slag, and finally cast at a temperature of 720° C. to obtain an ingot with a diameter of 85 mm.
[0084] The mixed gas is composed of 99% CO2 and 1% SF6 by volume; the mass ratio of the polished pure magnesium, the gadolinium in the polished magnesium-gadolinium master alloy, the zinc in the zinc particles and the polished TiB2 / Al master alloy is 88:9:1:2.
[0085] S3. Homogenization treatment: The ingot obtained in S2 is subjected to homogenization treatment at a temperature of 510° C. for 12 h. The treated ingot is air-cooled to room temperature (25° C.) to obtain an ingot.
[0086] S4. Extrusion treatment: The ingot obtained in S3 is hot extruded at a temperature of 410°C with an extrusion ratio of 18:1 to obtain an extruded rod with a diameter of 20 mm. The extruded rod is a Mg-Gd alloy (0.6wt.% TiB2-5.47wt.% Al2Gd) / Mg-9Gd-1.0Zn synergistically reinforced with LPSO and dual-scale particles, wherein the diameter of the Al2Gd micron particles is 1.1-12.3μm, and the diameter of the TiB2 nanoparticles is 70-110nm.
[0087] Comparative Example 1
[0088] This comparative example is a Mg-9Gd matrix alloy, which contains the following components in mass percentage: 9wt.% gadolinium, and the balance is magnesium; the preparation method of the Mg-9Gd matrix alloy in this comparative example is the same as the preparation method in Example 1, except that the addition of zinc particles is omitted to obtain the Mg-9Gd matrix alloy.
[0089] Structural and performance testing
[0090] 1. Microstructure analysis
[0091] Figure 1 The scanning electron microscope images of the Mg-9Gd matrix alloy, Mg-9Gd-1Zn, (0.6wt.%TiB2-5.47wt.%Al2Gd) / Mg-9Gd and (0.6wt.%TiB2-5.47wt.%Al2Gd) / Mg-9Gd-1.0Zn alloys prepared in Comparative Example 1, Examples 4, 6 and 8, wherein (a) is the scanning electron microscope image of the Mg-9Gd matrix alloy prepared in Comparative Example 1; Scanning electron microscope images, (b) is a scanning electron microscope image of the extruded Mg-9Gd-1Zn alloy of Example 4, (c) is a scanning electron microscope image of the extruded (0.6wt.%TiB2-5.47wt.%Al2Gd) / Mg-9Gd alloy of Example 6, (d) is a scanning electron microscope image of the extruded (0.6wt.%TiB2-5.47wt.%Al2Gd) / Mg-9Gd-1Zn alloy of Example 8. Figure 1 It can be seen that when Zn element and TiB2 particles are added in combination, the volume fraction of the second phase in the alloy is the largest.
[0092] 2. Room temperature strength test
[0093] The extruded alloys obtained in Examples 4, 6, 8 and Comparative Example 1 were subjected to room temperature tensile property tests, and the obtained tensile yield strength, tensile strength and fracture strain results are shown in Table 1.
[0094] Table 1 Performance test of extruded alloy at room temperature
[0095]
[0096] Figure 2 These are the tensile engineering stress-strain curves of Mg-9Gd, Mg-9Gd-1.0Zn, (0.6wt.% TiB2-5.47wt.% Al2Gd) / Mg-9Gd, and (0.6wt.% TiB2-5.47wt.% Al2Gd) / Mg-9Gd-1.0Zn alloys prepared in Comparative Example 1, Examples 4, 6, and 8 at room temperature.
[0097] According to Table 1, compared with the base alloy of Comparative Example 1, the room temperature tensile strength and yield strength of the alloy prepared in Example 4 are increased by 65 MPa and 72 MPa, respectively. This shows that LPSO effectively improves the room temperature mechanical properties of the Mg-Gd alloy. Compared with the base alloy of Comparative Example 1, the room temperature tensile strength and yield strength of the alloy prepared in Example 6 are increased by 32 MPa and 23 MPa, respectively. It can be concluded that TiB2 particles and Al2Gd particles effectively improve the room temperature mechanical properties of the Mg-Gd alloy. The room temperature tensile strength and yield strength of the alloy prepared in Example 8 are 317 MPa and 243 MPa, respectively, which are 94 MPa and 78 MPa higher than those of the base alloy of Comparative Example 1. At the same time, compared with the alloys in Examples 4 and 6, the room temperature tensile strength and yield strength are also significantly improved, indicating that the composite addition of LPSO, TiB2 nanoparticles and Al2Gd micron particles has a greater effect on improving the mechanical properties of the alloy than adding LPSO or TiB2+Al2Gd particles alone. At the same time, according to Figure 2 It can be seen that after the composite addition of LPSO, TiB2 nanoparticles and Al2Gd micron particles, the alloy can maintain good plasticity. Based on the above results, it can be seen that LPSO and dual-scale particles have the best effect on improving the performance of Mg-Gd alloys.
[0098] 3. High temperature strength test
[0099] The extruded alloys obtained in Example 8 and Comparative Example 1 were subjected to high temperature tensile property tests at different temperatures, and the tensile yield strength, tensile strength and fracture strain were statistically analyzed. The results are shown in Table 2.
[0100] Table 2 Performance test of extruded alloy at different temperatures
[0101]
[0102] Figure 3 Tensile engineering stress-strain curves at 200°C for the Mg-9Gd matrix alloy prepared in Comparative Example 1 and the (0.6wt.% TiB2-3.71wt.% Al2Gd) / Mg-9Gd-1.0Zn alloy prepared in Example 8.
[0103] Figure 4 Tensile engineering stress-strain curves at 250°C for the Mg-9Gd matrix alloy prepared in Comparative Example 1 and the (0.6wt.% TiB2-3.71wt.% Al2Gd) / Mg-9Gd-1.0Zn alloy prepared in Example 8.
[0104] Figure 5Tensile engineering stress-strain curves at 300°C of the Mg-9Gd matrix alloy prepared in Comparative Example 1 and the (0.6wt.% TiB2-3.71wt.% Al2Gd) / Mg-9Gd-1.0Zn alloy prepared in Example 8.
[0105] By comparing the high temperature tensile performance data of Example 8 and Comparative Example 1 at 200°C, 250°C and 300°C in Table 2, it can be concluded that after the introduction of LPSO, TiB2 nanoparticles and Al2Gd microparticles into the Mg-9Gd alloy, the high temperature strength of the alloy is significantly improved. The tensile strength and yield strength of the (0.6wt.%TiB2+3.71wt.%Al2Gd) / Mg-9Gd alloy of Example 8 at 200°C are 390MPa and 303MPa, respectively, which are 90MPa and 77MPa higher than those of the Mg-9Gd matrix alloy (300MPa, 226MPa), respectively. The tensile strength and yield strength of the (0.3wt.% TiB2+1.85wt.% Al2Gd) / Mg-9Gd-1.0Zn alloy of Example 8 at 250°C are 290MPa and 200MPa, respectively, which are 56MPa and 18MPa higher than those of the Mg-9Gd matrix alloy (234MPa, 182MPa), respectively. The tensile strength and yield strength of the (0.6wt.% TiB2-3.71wt.% Al2Gd) / Mg-9Gd-1.0Zn alloy prepared in Example 8 at 300°C are 224MPa and 196MPa, respectively, which are 21MPa and 38MPa higher than those of the Mg-9Gd matrix alloy (203MPa, 158MPa), respectively. At the same time, according to Figure 3 to Figure 5 It can be seen that the alloy prepared in Example 8 also has good plasticity at high temperatures.
[0106] In summary, the present invention introduces micron Al2Gd particles and nano TiB2 particles into the Mg-Gd alloy by adding zinc particles and nano TiB2 / Al master alloy, and also generates LPSO by reaction. On the one hand, the introduction of dual-scale particles avoids the problems of surface contamination, poor dispersion uniformity, and poor wettability of nano TiB2 particles. In the prepared composite material, the interface between TiB2 particles and α-Mg matrix is clean and continuous, and the lattice matching relationship is good, which can effectively strengthen the magnesium alloy; the dual-scale particles can be used as the heterogeneous nucleation core of α-Mg, which plays a role in refining the matrix structure and improving the size and distribution of the second item. On the other hand, the LPSO phase is a strengthening phase with high hardness and high modulus. It not only has a good second phase strengthening effect, but also has good plasticity. It twists during deformation to form a dislocation wall, which can further pin dislocations. The introduction of LPSO and dual-scale TiB2-Al2Gd particles refines the cast structure of the Mg-Gd alloy, and improves the room temperature and high temperature strength of the Mg-Gd alloy by pinning dislocation movement and hindering grain boundary sliding. The LPSO and dual-scale particle synergistically reinforced Mg-Gd alloy prepared by the present invention have good room temperature and high temperature mechanical properties, low preparation cost, and broad application prospects.
[0107] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A Mg-Gd heat-resistant alloy synergistically reinforced by LPSO and dual-scale particles, characterized in that: The invention comprises the following components in mass percentage: Gd 8.0-10.0wt.%, TiB2 0.3-0.9wt.%, Al2Gd 2.74-8.21wt.%, Zn 0.4-1.0wt.%, and the balance is Mg; wherein Al2Gd exists in the form of Al2Gd micron particles, and the TiB2 exists in the form of TiB2 nanoparticles.
2. The Mg-Gd heat-resistant alloy synergistically reinforced by LPSO and dual-scale particles according to claim 1, characterized in that: The particle size of the TiB2 nanoparticles is 70-110 nm, and the particle size of the Al2Gd micron particles is 1.1-12.3 μm.
3. The method for preparing the Mg-Gd heat-resistant alloy synergistically reinforced by LPSO and dual-scale particles according to claim 1 or 2, characterized in that: The following steps are involved: The magnesium, magnesium-gadolinium master alloy, zinc and TiB2 / Al master alloy are heated and melted, and the obtained alloy liquid is cast to obtain an ingot; The ingot is homogenized to obtain an ingot; The billet is hot extruded to obtain the Mg-Gd series heat-resistant alloy synergistically reinforced by the LPSO and the dual-scale particles.
4. The preparation method according to claim 3, characterized in that: The purity of the magnesium is above 99.8%; the magnesium-gadolinium master alloy is Mg-30wt.%Gd, and the purity of the magnesium-gadolinium master alloy is above 99.9%; the mass ratio of TiB2 to Al in the TiB2 / Al master alloy is 30:70; the zinc is zinc particles, and the purity of the zinc particles is above 99.8%; The mass ratio of gadolinium, zinc and TiB2 / Al master alloy in the pure magnesium and magnesium-gadolinium master alloy is (86.6-90.6):9:(0.4-1):(0-3), and the mass of the TiB2 / Al master alloy is not 0.
5. The preparation method according to claim 3 or 4, characterized in that: The preparation method of the TiB2 / Al master alloy comprises: ball milling TiB2 and aluminum powder and then hot pressing and sintering to obtain the TiB2 / Al master alloy; the rotation speed of the ball mill is 100r / min, and the ball-to-material ratio is 3:1; the temperature of the hot pressing and sintering is 630-650°C, and the time is 30-60min.
6. The preparation method according to claim 3, characterized in that: The heating and melting of magnesium, magnesium-gadolinium master alloy zinc and TiB2 / Al master alloy comprises: firstly heating and melting magnesium under the protection of mixed gas, and then sequentially adding magnesium-gadolinium master alloy, zinc and TiB2 / Al master alloy for second heating and melting; The mixed gas includes CO2 and SF6, the volume fraction of CO2 in the mixed gas is 99%, and the volume fraction of SF6 is 1%; the temperature of the first heating and melting is 680-700°C; the temperature of the second heating and melting is 760-800°C.
7. The preparation method according to claim 3, characterized in that: The casting temperature is 720-730°C.
8. The preparation method according to claim 3, characterized in that: The homogenization treatment was carried out at a temperature of 510° C. and for a period of 12 h.
9. The preparation method according to claim 3, characterized in that: The temperature of the hot extrusion is 410° C., and the extrusion ratio is 18:
1.
10. The preparation method according to claim 3, characterized in that: The magnesium, magnesium-gadolinium master alloy and TiB2 / Al master alloy are polished before use.
Citation Information
Patent Citations
Multi-nanophase composite enhanced magnesium alloy and preparation method thereof
CN105506426A
Magnesium-based composite material with improved heat resistance and preparation method thereof
CN114277297A
Micro-nano dual-scale particle reinforced Mg-Y series heat-resistant alloy and preparation method thereof
CN117187653A
Multi-scale particle reinforced Mg-Gd series alloy and preparation method thereof
CN118222897A